PANDUAN RANCANG RUANG TERBUKA DI JALAN JAMIN GINTING - PANCUR BATU: Studi Kasus: Lapangan Sepak Bola - Ulil Fahmi; Beny O.Y Marpaung (Jurnal Koridor, 2018)
The football field located in the corridor of Jamin Ginting-Pancur Batu, District of Deli Serdang is one of open spaces in sub district of Pancur Batu, which both used as sport facility and place of feast celebration by the community. The football field has not been fully used since there are no facilities that can support the activities of the community. The football field is also often used in other activities, such as Pasar Malam that potentially damage the ground surface. The functional success of this open space can be achieved by redesign it by considering the proportion of aesthetics and functional aspects. The purpose of this research is to redesign the football field as an open space that can support the social activities of the community of Pancur Batu. This research will conduct by using descriptive-qualtative method. The research goal is to be a guideine that can be used to redesign the football field in Pancur Batu that fit the social activities of the community. By redesign the football field, it is expected to create an open space that can be an identity of the Jamin Ginting-Pancur Batu corridor.